Representasi Perempuan pada Desain Kemasan "Kiranti" - Senja Aprela Agustin; Acep Iwan Saidi; Triyadi Guntur Wiratmo (Wimba : Jurnal Komunikasi Visual, 2011)
Gender representation is often used as an attribute of a product differentiation in the current packaging design. One of the woman representation could be found on the packaging design of âKirantiâ, a herbal ready to drink which is better known as a traditional medicine by earlier Javanese culture. Kiranti as a text is combined by verbal and visual elements that are meaningful to the readers. How the representation of women and constructions as well as decoding by its consumer are the main questions of this research. Using of discourse analysis method, Kirantiâs text can be traced not only from the visualization, but also of ideas or opinions behind them, such as socio-cultural situation in which Kiranti disseminated. In addition, consideration of readers position as consumers are very important in interpreting the text of Kiranti, because implified particular knowledge in society. Decoding by readers are diverse, ranging from the interpretation of the same message as producerâs intention, differences in interpretation, until modify its message. Visual and verbal elements that appear are the result of the selected signs combination by the producer of meaning, that seeks to utilize conventions that can be accepted easily by society. The combination of the signs are also affected by the construction of discourses, such as codes of Javanese culture, the concept of beauty and menstruating women, as well as the inherent characteristics of femininity (gender), that represented by visual elements, both graphic imagery (photography and illustration), typography, color, and form of the bottle form.